2020
DOI: 10.1002/ccr3.3402
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the subcutaneous tissue of catheterization site from the precatheterization state to the onset of anticancer drug‐induced induration: A case report

Abstract: This report presents some of the changes in the subcutaneous tissue at the site of catheter insertion of a patient undergoing chemotherapy. The site was observed by ultrasonography at 5 time points, namely, before insertion, immediately after treatment, after 1, 3, and 4 weeks. Some practice guidelines do not recommend the use of a peripheral intravenous catheter for irritant or vesicant continuous administration to avoid vessel damage. 1,2 However, peripheral intravenous catheters are unavoidably used in some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Fifteen participants had some remaining abnormal findings or developed new abnormal findings in the subcutaneous tissue by the next treatment day, and eight of these participants had no subjective symptoms or induration. One previous case study reported a risk of overlooking subcutaneous damage on the next treatment day (1 week later) in a patient receiving weekly chemotherapy via a PIVC (Abe‐Doi et al, 2020b). The current study has now revealed that subcutaneous damage may be overlooked by conventional observation even 28 days after prior chemotherapy administration.…”
Section: Discussionmentioning
confidence: 99%
“…Fifteen participants had some remaining abnormal findings or developed new abnormal findings in the subcutaneous tissue by the next treatment day, and eight of these participants had no subjective symptoms or induration. One previous case study reported a risk of overlooking subcutaneous damage on the next treatment day (1 week later) in a patient receiving weekly chemotherapy via a PIVC (Abe‐Doi et al, 2020b). The current study has now revealed that subcutaneous damage may be overlooked by conventional observation even 28 days after prior chemotherapy administration.…”
Section: Discussionmentioning
confidence: 99%